2014
DOI: 10.1073/pnas.1402604111
|View full text |Cite|
|
Sign up to set email alerts
|

Protective role of miR-155 in breast cancer through RAD51 targeting impairs homologous recombination after irradiation

Abstract: Significance Cell survival after DNA damage relies on DNA repair, the abrogation of which causes genomic instability and development of cancer. DNA double-strand breaks are lesions induced by ionizing radiation (IR) and can be efficiently repaired by DNA homologous recombination, a system that requires RAD51 recombinase (RAD51). Here we show that overexpression of miR-155 in human breast cancer cells reduces the levels of RAD51 and affects the cellular response to IR. High miR-155 levels were associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
140
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(151 citation statements)
references
References 48 publications
10
140
1
Order By: Relevance
“…The present study observed that the phosphorylation levels of AKT and ERK representative of signaling pathway activation decreased subsequent to miR-155 silencing, but it has yet to be determined whether the mechanism involves the regulation of PTEN expression. However, it has been revealed that the role of miR-155 in tumors involves multiple aspects and miR-155 interacts with the intracellular transcription factors regulating gene transcription (42,43). The present results demonstrated the ability of miR-155 to positively regulate the activity of NF-κB and AP-1.…”
Section: A B C D E Fsupporting
confidence: 55%
“…The present study observed that the phosphorylation levels of AKT and ERK representative of signaling pathway activation decreased subsequent to miR-155 silencing, but it has yet to be determined whether the mechanism involves the regulation of PTEN expression. However, it has been revealed that the role of miR-155 in tumors involves multiple aspects and miR-155 interacts with the intracellular transcription factors regulating gene transcription (42,43). The present results demonstrated the ability of miR-155 to positively regulate the activity of NF-κB and AP-1.…”
Section: A B C D E Fsupporting
confidence: 55%
“…The cells were seeded onto a 6-well plate at a density of 3x10 5 /well overnight. The cells were then collected and HK activities were measured using the Hexokinase Colorimetric Assay kit (Sigma-Aldrich China, Inc.), according to the manufacturer's protocol.…”
Section: Ionizing Radiation Treatment Approximately 5x10mentioning
confidence: 99%
“…The cells were seeded onto a 6-well plate at a density of 3x10 5 /well, and the culture medium was replaced with low glucose DMEM (Invitrogen; Thermo Fisher Scientific, Inc.) after 6 h. The concentrations of glucose and L-lactate were measured after a further 24 h using a Glucose Test kit (Applygen Technologies, Inc., Beijing, China) and an L-lactate Assay kit (Eton Bioscience, Inc., San Diego, CA, USA), respectively, according to the manufacturer's instructions.…”
Section: Ionizing Radiation Treatment Approximately 5x10mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have identified some novel miRNAs which are involved in the DNA repair pathway and regulate the DNA damage response to radiation (29)(30)(31). Yan et al (32) identified miR-101 as a molecule able to sensitize cancer cells to IR by targeting the 3'UTR of DNA-PKcs and ATM transcripts.…”
Section: Discussionmentioning
confidence: 99%